INVENTARISASI KAYU AJANG KELICUNG (Diosphyros macrophylla) di BKPH SEJORONG MATAIYANG KABUPATEN SUMBAWA BARAT - saleha; Baiq Mirawati; Muhammad Sadir; Baiq Arriyadul Badi’ah (Jurnal Silva Samalas, 2026)
The population of ajang kelicung wood (Diospyros macrophylla) is increasingly threatened by escalating pressures on forest resources. The primary threats stem from human activities, including illegal logging, land conversion, and environmental degradation. This study aims to assess the population of Diospyros macrophylla in the BKPH Sejorong Mataiyang area. The method employed was cluster sampling technique, utilizing 10 sample plots each measuring 100 m × 100 m. The parameters measured in this study included branch-free height, diameter, and total height of all Diospyros macrophylla trees across a 200 ha area. The results revealed that, out of the ten observed plots, Diospyros macrophylla was present in only six. A total of 103 individuals were recorded in these six plots, whereas the remaining four plots lacked any population of this species due to conversion into agricultural land by local communities. This conversion was facilitated by the area’s designation as limited production forest in Desa Talonang Baru, which permits land utilization. Further vegetation analysis indicated that the relative density of this species was 10.32%, falling into the low category; however, it exhibited a very high relative frequency of 107%. The combination of these values yielded an Importance Value Index (INP) of 117.32%, signifying a high ecological role for Diospyros macrophylla despite its quantitatively sparse population.